Method validation for determination of lead and cadmium in natural water using flame atomic absorption spectrometry (FAAS) - Poolkasem, Angwara; changthong, Neeranart (Bulletin of Applied Sciences, 2022)
The method validation for determination of lead and cadmium in natural water, i.e. deep well water, rain and river water was investigated by flame atomic absorption spectrometry using the modified method based on AWWA 21st Ed., 2005 prior to the use in routine work. The characteristics of the method showed that the linear range of lead (Pb) and cadmium (Cd) were 0.1 – 1.5 mgL-1 and 0.02 -0.5 mgL-1, the detection limits were 0.02 and 0.005 mgL-1, and the limits of quantitation were 0.1 mgL-1 and 0.02 mgL-1, respectively. Percentage recovery of lead and cadmium were 91-110% and 98-105% respectively. Relative standard deviations for both elements were between 0.8-3.2. The percentage recovery and relative standard deviation were within acceptance limit. In addition, the percentage measurement uncertainties at 95% confidence level of cadmium and lead were less than 15% throughout concentrations of working range that subjected to the target uncertainty. Therefore, this validated method was fit for the intended use.